Answer:
(x+11)^2 + (y+8)^2 = 4^2/16
(x+6)^2 + (y+15)^2 = 5
Explanation:
the standard equation of a circle is
(x-h)^2 + (y-k)^2 = r^2 where (h,k) is the center and r is the radius
in the first equation -11 is h and -8 is k
so (x+11)^2 because when you subtract a negative the double negative creates a positive and that’s the same for (y+8)^2
so (x+11)^2 + (y+8)^2 = 4^2 or 16
in the second equations -6 is h and -15 is k
and the double negative is also effective in this equation so (x+6)^2 and (y+15)^2 therefore, (x+6)^2 + (y+15)^2 = 5 (the square root of 5 squared is just 5)
hope this helps :)